Current Sensorless Control Algorithm for Single-Phase Three-Level NPC Inverter - Suzdalenko, Alexander; Zakis, Janis; Steiks, Ingars (Electrical, Control and Communication Engineering, 2014)
The current measurement is becoming a challenging task in power converters operating at high switching frequencies, moreover traditional control system requires two control loops - first (slow) regulates DC-link voltage, second (fast) controls the shape of current, that all together results in complicated transfer function and long transition periods. The current sensorless control (CSC) allows neglecting the mentioned problems. This research for the first time presents the solution of CSC implementation in single-phase three-level neutral point clamped inverter. Mathematical equations were defined for inductor current peaks and transistor conduction time during discontinuous and continuous conduction modes, as well as major problem of current fitting between different voltage levels (consequently with different current peak-to-peak values) was solved, providing two solutions - pre-fitting and post-fitting trajectories. The verification of our theoretical assumptions and analytical equations was confirmed by the simulation analysis. Challenges of real experiments are discussed in the conclusion.